P PENGARUH RELAKSASI PERNAFASAN TERHADAP INTENSITAS NYERI PERSALINAN KALA 1 DI KLINIK KASIH IBU KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2022 - Nur Mala Sari; Erlina Hayati; nurul Aini; ade Putri Ritonga (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
ABSTRACT Childbirth is the most awaited thing by pregnant women, but on the other hand it is a thrilling thing. Pain that makes the desired happiness filled with fear and anxiety. Several studies have shown that primitive people experience longer and painful labor, while people who have advanced give birth without pain and most (90%) deliveries are accompanied by pain (Elly S, 2017). Pain during labor has an impact on increasing the activity of the sympathetic nervous system which results in nausea and vomiting, excessive sweating, and changes in blood pressure, pulse, breathing, and skin color. One effort to minimize labor pain is to use breathing relaxation techniques. This study aims to determine the effect of breathing relaxation techniques on reducing labor pain in the first stage of the active phase. The type of design used in this study was pre-experimental with one group pretest-posttest design. The number of samples is 10 respondents. The technique of collecting sample data using purposive sampling method. Data collection techniques used a questionnaire and a Numeric Rating Scale (NRS) pain scale. From the results of the data before being given the deep breathing relaxation technique with a score of 2.60 (SD: 0.699) (min: 2) (max: 4) while after being given the breathing relaxation technique the score was 2.50 (SD: 0.707) (min: 1) (max: 3) means that inpartu mothers experience a decrease in labor pain in the active phase of the 1st stage. Wilcoxon test results obtained a Z value of 2.598 with a significant value of 0.009 < (0.05). So that H0 is rejected and Ha is accepted, this shows that there is an effect of deep breathing relaxation techniques on reducing labor pain in the active phase of the 1st stage at the Kasih Ibu Clinic, Deli Tua District, Deli Serdang Regency in 2022. Keywords: Breathing Relaxation Technique, First Stage of Labor Pain, Active Phase.